Modified Printed Dipole With Reflector And Director - Abu Hussin, Farhana; Ahmad, Badrul Hisham; Abd. Aziz, Mohamad Zoinol Abidin; Suaidi, Mohamad Kadim (Penerbit UTM Press, 2016)
This paper presented the design for dipole antenna at 2.4GHz for wireless local area network (WLAN) application. This design aimed to improve the antenna gains and directivity. The printed dipole with reflector and director was designed and simulated using CST Microwave Studio. In this design, a metallic reflector was added in order to increase the gain. The director was added to the structure to maximize the antenna directivity. The simulation results showed that the antenna achieved a maximum gain of 5dB for the modified design and 6dBi for the directivity. Other antenna parameters were also investigated such as bandwidth, radiation pattern, and return los.